Seroprevalence of Hepatitis-B Virus and Evaluation of DNA Extraction Methods from Dried Blood Spot on Filter Paper for Molecular Testing in Kaduna State, Nigeria - Mohammed Ibrahim Tahir * , Ahmed Babangida Suleiman and Abdurrahman El-Fulaty Ahmad (Sokoto Journal of Medical Laboratory Science)
Hepatitis B is a potentially life-threatening disease caused by hepatitis B virus. This study was a cross sectional and included a total of 300 paired blood samples collected in tube and on filter paper from students from three secondary schools located across the three senatorial zones of Kaduna State, Nigeria from April 2015 to July 2015. Hepatitis B surface antigens were detected in sera by enzyme linked immunosorbent assay (ELISA) and DNA extracted from DBS from some seropositive samples were detected by PCR technique for hepatitis B virus polymerase gene. The overall seroprevalence of Hepatitis B surface antigen was found to be 18.33%. The mean concentrations for Microwave extraction, Phenol-Chloroform and Zymo Research Viral DNA Kit™ methods were 1219.00ng/µl, 528.85 ng/µl and 9.14 ng/µl respectively. Polymerase gene was detected among 40% of individuals that showed seropositivity to Hepatitis B surface antigen. This study has demonstrated a high prevalence of hepatitis B virus antigenaemia among Secondary School students in Kaduna State, Nigeria. Our study provides evidence that hepatitis B virus infection is highly endemic in the studied area therefore, posing a threat of high incidence of cirrhosis and hepatocellular carcinoma.